Synthesis, pharmacokinetic studies, and metabolite analysis of meridianin C in rats using a validated ultra high performance liquid chromatography-tandem mass spectrometry method - Xu, Liangyu; Wu, Zhaogen; Ramachandraiah, Karna; Jiang, Guihun; Zhang, Guozhe (Frontiers in Pharmacology, 2025)
IntroductionMeridianin C (MC) is a marine-derived indole alkaloid that has demonstrated kinase inhibitory and anti-tumor activities. Despite its diverse biological properties, no previous reports have systematically evaluated the in vivo quantitative analysis of MC and its metabolites.MethodsIn this study, MC was synthesized following a previously reported procedure with slight modifications. A sensitive, accurate, and reliable ultra-high performance liquid chromatography-tandem mass spectrometry (UHPLC–MS/MS) method was developed to simultaneously detect MC and its five major metabolites (MC-1-N-O-GluA, MC-1-N-O-SO3H, MC-2′-N-O-GluA, MC-2′-N-O-SO3H, and MC-O-GluA-didehydration) in rat plasma. Rats received a single oral dose of MC (100 mg/kg), and pharmacokinetic analysis was subsequently performed.ResultsPharmacokinetic data revealed that MC was rapidly absorbed, with a Cmax of 44.8 ± 7.0 μmol/L, an AUC0–48h of 232.0 ± 85.9 μmol·h/L, a Tmax of 0.75 ± 0.27 h, and a t1/2 of 17.7 ± 14.1 h. Plasma concentrations of MC were significantly higher than those of its metabolites, suggesting that MC remains the predominant circulating form after oral administration. The identified metabolites mainly resulted from hydroxylation combined with glucuronide conjugation, hydroxylation combined with sulfation, and hydration combined with glucuronide conjugation.DiscussionThese findings demonstrate that the primary metabolic pathway of MC involves hydroxylation (phase I) followed by conjugation (phase II). To our knowledge, this represents the first systematic investigation of the pharmacokinetic characteristics of MC and its metabolites in rats. The study not only advances understanding of MC disposition but also provides a valuable reference for future pharmacokinetic evaluations of other marine-derived indole alkaloids.